Recent trends in car usage in advanced economies: Slower growth ahead? ; summary and conclusions - Kurt Van Dender; Martin Clever (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
Over the past 10 to 15 years, the growth of passenger vehicle travel volumes has decelerated in several high-income economies and, in some, growth has stopped or turned negative. Drawing from work presented to and discussions at the ITF Roundtable on long-run trends in travel demand, held in November 2012, this paper presents evidence on known causes of this change in growth rates and discusses knowledge gaps, hypothetical explanations and policy implications.
Keywords: 330; Motorisierter Individualverkehr; Industrieländer